Industrial Training Report: Perbadanan Perpustakaan Awam Terengganu / Noor Maziah Mat Amin - Mat Amin, Noor Maziah (Faculty of Information Management, 2018)
Terengganu Public Library is a statutory body of the state. It was established at 1974. Chapter 1 are explained about the history of Terengganu Public Library. In chapter 2, it tells about the organization information in Terengganu Public Library. There are 3 main department consist of collection development and management department, library services and information department and library network departments. For the supports department, it is consists of management services department which the sub- unit of human resource and administrative unit, financial unit, information and technology unit, maintenance unit, corporate planning and development unit and Terengganu language center. In chapter 3, it explain more about the activities during the industrial training and also it consists of the special projects that conducted by the students for 5 months of the training. Besides that, for chapter 4, it is focused on the knowledge gained by the student, personal opinion of the organization, lesson learnt and the limitation faced in the organization. However, chapter 4 also provided the recommendation in order to solve the problems occurred in the organizations. For the last chapter which is chapter 5, it is the overall summary of the industrial training for 5 months at Terengganu Public Library.